Cosmic evolution of AGN with moderate-to-high radiative luminosity in the COSMOS field. Issue Volume 12:Issue S333(2017) (8th May 2018) - Ceraj, L.; Smolčić, V.; Delvecchio, I.; Delhaize, J.; Novak, M.
Abstract: We study the moderate-to-high radiative luminosity active galactic nuclei (HLAGN) within the VLA-COSMOS 3 GHz Large Project. The survey covers 2.6 square degrees centered on the COSMOS field with a 1σ sensitivity of 2.3 μJy/beam across the field. This provides the simultaneously largest and deepest radio continuum survey available to date with exquisite multi-wavelength coverage. The survey yields 10, 830 radio sources with signal-to-noise ratios ≥5. A subsample of 1, 604 HLAGN is analyzed here. These were selected via a combination of X-ray luminosity and mid-infrared colors. We derive luminosity functions for these AGN and constrain their cosmic evolution out to a redshift of z ∼ 6, for the first time decomposing the star formation and AGN contributions to the radio continuum emission in the AGN. We study the evolution of number density and luminosity density finding a peak at z ∼ 1.5 followed by a decrease out to a redshift z ∼ 6.